2012
DOI: 10.1063/1.4733953
|View full text |Cite
|
Sign up to set email alerts
|

The ferromagnetic and antiferromagnetic phases in anion deficient La0.5−xPrxBa0.5CoO3−δ cobaltites

Abstract: Creeping of minor hysteresis loops in Co thin films J. Appl. Phys. 112, 063919 (2012) Invariance of the magnetization axis under spin reorientation transitions in polycrystalline magnets of Nd2Fe14B J. Appl. Phys. 112, 063918 (2012) Procedure for numerical integration of the magnetocaloric effect J. Appl. Phys. 112, 063920 (2012) Vortex dynamics in triangular-shaped confining potentialsNeutron powder diffraction studies of crystal and magnetic structures, magnetization and magnetotransport measurements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(75 reference statements)
1
18
0
2
Order By: Relevance
“…6) can be ascribed to field induced spin state transition from antiferromagnetic into ferromagnetic phase. 7,8 This transition was suggested to occur via structural distortion induced by magnetic field. 7,8 The structural distortion stabilizes the IS state and destabilizes both HS and LS states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) can be ascribed to field induced spin state transition from antiferromagnetic into ferromagnetic phase. 7,8 This transition was suggested to occur via structural distortion induced by magnetic field. 7,8 The structural distortion stabilizes the IS state and destabilizes both HS and LS states.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen deficit stabilizes an antiferromagnetic phase in both La 0.5 Ba 0.5 CoO 3-d and La 0.5 Sr 0.5 CoO 3-d series. [6][7][8] It was suggested that the magnetic moment of 1.5 l B in metallic La 0.5 Sr 0.5 CoO 3 can be rationalized with an intermediate-spin model having localized t 5 2g configurations on each cobalt ion and an narrow itinerant r* band containing 0.5 electrons per Co atom magnetized ferromagnetically. 9 However, according to Refs.…”
mentioning
confidence: 99%
“…Dry pure La 2 O 3 , BaCO 3 , Co 3 O 4 , CuO, ZnO, Cr 2 O 3 , Ni 2 O 3 , TiO 2 and RuO 2 powders were well mixed in the stoichiometric amounts and initially decarbonated in the air at 1170 K for 20 h. After regrinding, the samples were fired in the air at 1470 K for 15 h and slowly cooled for several times [4,23]. The cooling rate is 30 K/h.…”
Section: Methodsmentioning
confidence: 99%
“…The origin of the ferromagnetic state in metallic cobaltites has been a subject of discussion for a long time. One knows that cobaltites are extremely sensitive to order-disorder, doping, temperature, and crystal structure [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The substitution of other ions for Co ions could directly modify the magnetic ordering and facilitate understanding the nature of the ferromagnetic state as well as clarifying the spin state of Co ions.…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что наши XMCD результаты на L 2,3 -краях хорошо согласуются и дополняют данные, ранее полученные методом XMCD в [13], а также данные представленые в работе по неупругому нейтронному рассеянию [11], нейтронной дифракции и EXAFS [20][21][22][23].…”
Section: рисunclassified